1982
DOI: 10.1093/bja/54.8.865
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia for Outpatient Termination of Pregnancy

Abstract: Inhalation anaesthesia with enflurane was compared with i.v. fentanyl for outpatient termination of pregnancy. Blood loss was greater in the enflurane group with a geometric mean loss of 73.0 ml compared with 43.9 ml in the fentanyl group. There was a greater frequency of nausea nd vomiting in the fentanyl group and no reduction in abdominal pain or need for analgesia after operation. A close relationship was found between blood loss and duration of the procedure but not between blood loss and gestational age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Also, some patients may be thought unsuitable for day care; a comparison of different techniques of general anaesthesia for minor gynaecological day surgery (Towey et al 1979) showed that over a quarter of patients have headache and nausea when they return home and about half do not feel like returning to normal activities the next day. Gestational age, according to another study by anaesthetists (Hackett et al 1982), is much less important than duration of operation in determin-ing blood loss at termination.…”
Section: O M M E N T a R Ymentioning
confidence: 95%
“…Also, some patients may be thought unsuitable for day care; a comparison of different techniques of general anaesthesia for minor gynaecological day surgery (Towey et al 1979) showed that over a quarter of patients have headache and nausea when they return home and about half do not feel like returning to normal activities the next day. Gestational age, according to another study by anaesthetists (Hackett et al 1982), is much less important than duration of operation in determin-ing blood loss at termination.…”
Section: O M M E N T a R Ymentioning
confidence: 95%